The problems with reconstruction of first mass series buildings - Osipov А.; Lyeka, D. (Ways to Improve Construction Efficiency, 2019)
The article deals with the problem of reconstruction and modernization of residential houses of the first mass series. Analysis of world experience in the reconstruction of buildings of the first mass series. Economic expediency of reconstruction of buildings of the first mass series. Proposals for redevelopment of apartments in these buildings, and perception of redevelopment as a basis for the development of rational methods of technology for the reconstruction of buildings of the first mass series.